Exome Sequencing Reveals Diagnosis of LAMA2-Muscular Dystrophy and Possibility of Coexisting Bethlem Myopathy in a Neonate - Bajaj, Shruti; Shah, Piyush; Seenappa, Venu; Kalyankar, Jayashree; Hingwala, Divyata (Journal of Pediatric Neurology, 2021)
We reported a neonate presenting with muscle weakness, hypotonia, and joint contractures since birth. Investigations revealed significantly elevated creatinine-phosphokinase, abnormal electromyography suggestive of muscle disease and normal magnetic resonance imaging (MRI) of the brain. Exome sequencing revealed homozygous pathogenic mutations in LAMA2 (NM_000426.3: c.7881T > G, p.(His2627Gln)) and a heterozygous likely-pathogenic mutation in COL6A2 (NM_001849.3: c.1970–2A > G). Parental segregation by Sanger sequencing confirmed a heterozygous carrier state for the LAMA2 variant in both parents, thus confirming the diagnosis of autosomal recessive LAMA2-muscular dystrophy (LAMA2-MD) in the proband. The COL6A2 variant segregated with the as-yet asymptomatic mother. Musculoskeletal MRI of the proband at 12 months of age revealed peripheral involvement of the vastii, rectus femoris, gastrocnemius and the soleus, with relative central sparing, without areas of fatty infiltration; not serving to distinguish clearly between LAMA-MD and COL6A2- related disease. Reverse phenotyping of a 27-year-old mother revealed a normal musculoskeletal MRI and clinically absent red flags. Potential explanations for the heterozygous likely-pathogenic COL6A2 variant in the proband and the mother include (a) a coexisting diagnosis of autosomal dominant COL6A2-related myopathy, likely Bethlem myopathy, which has a variable clinical phenotype and age of onset; (b) a carrier state for autosomal recessive Ullrich congenital muscular dystrophy; or (c) a heterozygous COL6A2 variant contributing as a synergistic factor along with homozygous LAMA2 mutation. The couple was offered genetic counseling regarding the proband and the future pregnancies.
Keywords: next-generation sequencing; arthrogryposis; muscle disorders; genetic counseling; dual diagnosis